2014
DOI: 10.1016/j.bbrc.2014.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of hepatoma-derived growth factor-related protein-3 induces apoptosis of H1299 cells via ROS-dependent and p53-independent NF-κB activation

Abstract: We previously identified hepatoma-derived growth factor-related protein-3 (HRP-3) as a radioresistant biomarker in p53 wild-type A549 cells and found that p53-dependent induction of the PUMA pathway was a critical event in regulating the radioresistant phenotype. Here, we found that HRP-3 knockdown regulates the radioresistance of p53-null H1299 cells through a distinctly different molecular mechanism. HRP-3 depletion was sufficient to cause apoptosis of H1299 cells by generating substantial levels of reactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…It regulates the transcription of DNA, and mediates apoptosis in response to oxidative stress [38]. Recent studies have demonstrated that ROS-dependent NF-kB activation induced the protein expression of c-Myc and Noxa in p53-independent human NSCLC cell death [50]. On the contrary, NF-kB activation was involved in resistance to oxidative stress and p53-mediated programmed cell death [5153].…”
Section: Discussionmentioning
confidence: 99%
“…It regulates the transcription of DNA, and mediates apoptosis in response to oxidative stress [38]. Recent studies have demonstrated that ROS-dependent NF-kB activation induced the protein expression of c-Myc and Noxa in p53-independent human NSCLC cell death [50]. On the contrary, NF-kB activation was involved in resistance to oxidative stress and p53-mediated programmed cell death [5153].…”
Section: Discussionmentioning
confidence: 99%
“…For example, hepatoma‐derived growth factor‐related protein‐3, which has an anti‐apoptotic effect (Yun et al . ), was increased to 143.9% in the AMY (Fig. c).…”
Section: Resultsmentioning
confidence: 84%
“…There were also some protective factors activated after OVX. For example, hepatomaderived growth factor-related protein-3, which has an anti-apoptotic effect (Yun et al 2014), was increased to 143.9% in the AMY (Fig. 3c).…”
Section: Resultsmentioning
confidence: 95%
“…Drug resistance of lung cancer cells is mainly attributed to resistance to apoptotic cell death. Induction of apoptotic cell death is the main mechanism of action of agents used for the treatment of lung cancer (16). The redox status of cells may determine their viability.…”
Section: Discussionmentioning
confidence: 99%